PENGARUH VARIABEL EKONOMI MAKRO DAN KEUANGAN TERHADAP RISIKO SISTEMATIS INDUSTRI PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Akhmad Sodikin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
The Aim Of This Research Is To Analyzed Influence Of Macro Economics Variables Who Consist Of Economic Growth, Exchange, Inflation, And Financial Variables Who Consist Of Dol, Aset Growth And Debt Ratio To Systematic Risk In Agriculture Stock In Indonesia Stock Exchange From 2010 Untill 2013 Simultanously And Partially. Based On Agriculture Stocks Data Analyzed Known That Macro Economic Who Consist Of Ekonomic Growth, Exchange And Inflation And Financial Variables Whoc Consist Of Dol, Aset Growth And Debt Ratio Influenced To Systematic Risk In Agriculture Stocks Form 2010 Untill 2013 Simultanously. Otherwise Partially, Only Inflation Variables Didn’t Influence To Systematic Risk. The T Value Of That Variable Is -1,21, 0,23 Of Probality And More Than 0,05.